GP179 The incidence of infliximab infusions in paediatric IBD patients in a tertiary paediatric gastroenterology centre. (June 2019) - Gordon, Beth; Langa, Ciara; O'Driscoll, Karen; Kiernan, Siobhan; Bourke, Billy; Broderick, Annemarie; Hussey, Seamus
Abstract : Background: Infliximab is a chimeric monoclonal antibody that targets Tumour Necrosis Factor-a in inflammatory bowel disease (IBD). Our Lady's Children Hospital Crumlin is the sole tertiary paediatric gastroenterology service in Ireland caring for the IBD paediatric population. Our practice has been using the Infliximab originator, Remicade, for treatment. In our centre, for each patient commencing Infliximab treatment, we follow a specific protocol with regards to infusion rates, pre-medication and observation post infusion. Objectives: Our primary objective was to assess the incidence of adverse infusion reactions to Infliximab. Methods: We performed a retrospective analysis of patient charts who were on Infliximab infusions prior to the introduction of the biosimilar Infliximab infusion in October 2018 in our centre. We reviewed a cohort of 100 patients who received Infliximab infusions during the time period 1 st January 2016 to 30 th September 2018. We assessed for any ADR ranging from mild requiring medical review to severe, requiring rescue adrenaline for anaphylaxis, as documented in patient notes and medication charts. In view of practice changes to infusion rate times and evidence on exclusion of pre-medications, we aimed to investigate our current infusion adverse drug reactions (ADR) to compare going forward with the biosimilar switch. Results: In our cohort, 42% patients were female and 58% male. The majority 74% (n =74) of patients were diagnosed with Crohn's disease, whilst 25% (n =25) had a diagnosis of Ulcerative Colitis and 1% (n =1) with IBD-undetermined. The average age of diagnosis was 11.8 years (Range =3.4 - 16.4). 10% (n =10) of patients were commenced on Infliximab at diagnosis as inpatients with the remaining 90% attending as outpatients to the day ward. The overall incidence of Infliximab infusion reactions was 4% (n = 4). Significant severe non-anaphylactic infusion reaction, occurred in one patient only (1%). Of note, the patient did not receive adrenaline and was treated with IV hydrocortisone and IV chlorphenamine as per the protocol. 2% (n=2) were classed as moderate reactions with rash and facial flushing, both given IV hydrocortisone. Mild reaction occurred in 1% (n=1) with an episode of central chest pain that warranted medical review and the infusion re-started with a slower rate. Conclusions: Infliximab Infusion reactions are rare and found in a small quantity among paediatric IBD patients. Going forward with the biosimilar switch in our centre we can compare this data to assess its safety profile.